PENERAPAN TEKNOLOGI AKUAPONIK PADA BUDIDAYA IKAN NILA (Oreochromis niloticus) DAN SELADA (Lactuca sativa) DI LAHAN YANG TERBATAS DI SENTRA WISATA KULINER DELES MERR, SURABAYA - Luthfiana Aprilianita Sari; Kismiyati Kismiyati; Rozi Rozi; Naufal Falatehan; Yogita Tirta Noviyanti; Auriga Putri Faradilla; Gita Zahrani Aryandini; Benedikta Tania Diklauia; Sulastri Arsad; Muhammad Yusuf (Jurnal Abdi Insani, 2023)
Tilapia is a consumable fish that is needed in large quantities so that cultivation is carried out with dense stocking. The disadvantage of dense stocking is that the cultivation waste from feces or residual feed is quite high so it is necessary to apply a technology, namely aquaponics. This technology is the basis for community service in a limited location at the Deles Merr Culinary Tourism Center, Surabaya. The aim is to provide knowledge about aquaponics which is a combined system of fish and vegetable farming. Fish feces and feed residue are useful as fertilizer for vegetables so that water quality becomes optimal. The community service was conducted through counseling and mentoring methods on the application of aquaponic technology for tilapia (O. niloticus) and lettuce (L. sativa) cultivation on limited land. The target to be achieved is to increase knowledge, empowerment and improve skills in producing fish and vegetable farming businesses. Assistance in the form of an observation study of the application of aquaponic technology for tilapia (O. niloticus) and lettuce (L. sativa) cultivation on limited land resulted in growth rate (GR) data of 1.2 gr/day and specific growth rate (SGR) of 0.05%/day. Lettuce plants absorb ammonia produced from feces and remaining tilapia feed, thus optimizing water quality which has an impact on growth rate and specific growth rate. The community has gained knowledge and applied aquaponic technology in tilapia (O. niloticus) and lettuce (L. sativa) farming.